2017
DOI: 10.1104/pp.17.00787
|View full text |Cite
|
Sign up to set email alerts
|

Novel Stress-Inducible Antisense RNAs of Protein-Coding Loci Are Synthesized by RNA-Dependent RNA Polymerase

Abstract: (S.S.); 0000-0001-8288-0467 (M.S.).Our previous study identified approximately 6,000 abiotic stress-responsive noncoding transcripts existing on the antisense strand of protein-coding genes and implied that a type of antisense RNA was synthesized from a sense RNA template by RNAdependent RNA polymerase (RDR). Expression analyses revealed that the expression of novel abiotic stress-induced antisense RNA on 1,136 gene loci was reduced in the rdr1/2/6 mutants. RNase protection indicated that the RD29A antisense R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 66 publications
(118 reference statements)
0
9
0
Order By: Relevance
“…Since only two out of 9,445 (0.02%) reads mapped antisense to the ERCC RNA Spike-In collection 11 and 0 of 19,665 reads mapped antisense to the highly expressed gene RUBISCO ACTIVASE ( RCA ) ( AT2G39730 ), we conclude that spurious antisense is rare or absent from nanopore DRS data. This simplifies the interpretation of authentic antisense RNAs, which is important in Arabidopsis because the distinction between RT-dependent template switching and authentic antisense RNAs produced by RNA-dependent RNA polymerases that copy mRNA is not straightforward 17 . For example, by nanopore DRS, we could identify Arabidopsis long non-coding antisense RNAs, such as those at the auxin efflux carriers PIN4 and PIN7 (Figure 1C, Supplementary figure 1G).…”
Section: Resultsmentioning
confidence: 99%
“…Since only two out of 9,445 (0.02%) reads mapped antisense to the ERCC RNA Spike-In collection 11 and 0 of 19,665 reads mapped antisense to the highly expressed gene RUBISCO ACTIVASE ( RCA ) ( AT2G39730 ), we conclude that spurious antisense is rare or absent from nanopore DRS data. This simplifies the interpretation of authentic antisense RNAs, which is important in Arabidopsis because the distinction between RT-dependent template switching and authentic antisense RNAs produced by RNA-dependent RNA polymerases that copy mRNA is not straightforward 17 . For example, by nanopore DRS, we could identify Arabidopsis long non-coding antisense RNAs, such as those at the auxin efflux carriers PIN4 and PIN7 (Figure 1C, Supplementary figure 1G).…”
Section: Resultsmentioning
confidence: 99%
“…The finding that 58 annotated MIRNAs are downregulated in rdr1/2/6 mutant plants suggests that RDR1, RDR2, and RDR6 may have redundant roles in regulating processes that were not previously uncovered by studying RDR1, RDR2, or RDR6 alone. Similarly, another study found that loss of RDR1/2/6 reduces the expression of antisense RNAs during plant response to abiotic stresses, and TAS2 antisense RNAs were lower in rdr1/6 , rdr2/6 , or rdr1/2/6 mutant plants when compared with rdr6 single-mutant plants [ 62 ]. These findings reveal that RDR1/2/6 regulate the abundance of stress-related antisense RNAs cooperatively, but this functionality is separate from RDR6 functionality in siRNA biogenesis due to the fact that TAS2 was still found to accumulate in the absence of RDR6 function ( rdr6 mutation).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, OsRDR4 should be involved in RNA interference and silencing: RNA-dependent RNA polymerases (RDRs), in fact, are the core proteins mediating RNA interference as they can amplify microRNAs and small temporal RNAs and can also produce double-stranded RNA using small interfering RNAs as primers [ 158 ]. In addition, RDRs have antisense RNA synthesis activity independent of the endogenous small RNA pathways [ 159 ]. Quite interestingly, OsRDR4 expression appears to be quite specific, as it does not show detectable levels in vegetative tissues except the shoot apical meristem [ 158 ].…”
Section: Discussionmentioning
confidence: 99%